(NpEDAGOG)QÆKA (B:s)E (NNAW^ALXNIJ POS)QÆBNIKs)E ((NkI)QÇW (B:s)E (NoSW)QÆTA uKRAÇNIs)E (NkI)QÇW (B:s)E (Nknt(B,s, 2008)
(Nw POS)QÆBNIKU WIKLADENÆ TEORETI^NÆ OSNOWI PEDAGOGÆKI QK NAUKI(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpEDAGOG)QÆKAs)E; (NZAPITANNQs; (NMORALXs; (NWIHOWANNQs; (NWIZNANNQs